Benign fibrous histiocytoma of the fronto-temporo-parietal region: a case report and review of the literature - Chen, Hongxu (Int J Clin Exp Pathol, 2015)
Primary benign fibrous histiocytoma (BFH) at the skull is extremely rare. Here we report a case of a 22-year-old man presented with a 1-year history of progressive enlargement subcutaneous mass on the right side of the fronto-temporo-parietal region without symptoms. The tumor was radical resected through craniotomy and the bone defect was repaired by pre-plasticity titanium mesh. Histopathologic examination confirmed a benign fibrous histiocytoma, and no signs of tumor recurrence were detected at 3-year follow-up.